Large Gain, Low Noise Nanocomposite Ultraviolet Photodetectors with a Linear Dynamic Range of 120 dB. Issue 4 (28th February 2014) - Fang, Yanjun; Guo, Fawen; Xiao, Zhengguo; Huang, Jinsong
<x xml:space="preserve">Abstract</x> A fullerene‐based nanocomposite photodetector with peak quantum efficiency over 400% and specific detectivity of 6.5 × 1012 Jones at a wavelength of 390 nm is enabled by a cross‐linked polymer:ZnO nanocomposite buffer layer. The introduced ZnO nanoparticles not only increase the photoconductive gain through a trap‐controlled electron injection mechanism, but also effectively reduce the noise current, yielding a record linear dynamic range (LDR) of 120 dB. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>